2013
DOI: 10.2478/s11536-012-0115-8
|View full text |Cite
|
Sign up to set email alerts
|

Infections of external ventricular drainages

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…Not surprisingly, we found that infections occurred significantly earlier in patients with EVD compared with those with a VP shunt. Although our data are comparable with the results of other authors [ 5 , 22 , 27 , 31 ], comparisons have to be interpreted with caution because of the small numbers of patients.…”
Section: Discussionsupporting
confidence: 87%
“…Not surprisingly, we found that infections occurred significantly earlier in patients with EVD compared with those with a VP shunt. Although our data are comparable with the results of other authors [ 5 , 22 , 27 , 31 ], comparisons have to be interpreted with caution because of the small numbers of patients.…”
Section: Discussionsupporting
confidence: 87%
“…The infection rate did not increase even if the catheterization time exceeded 10 days, with an average infection time of 8.6 days. Strojnik et al (18) reported that the average indwelling time of an EVD tube was 7.41 ± 3.26 days, and he considered that day 7 is the crucial time for the indwelling of EVD. He reported that the infection rate at <7 days was 9.46% and that at >7 days, it was 23.44%.…”
Section: Discussionmentioning
confidence: 99%
“…Tačiau, kaip ir kiekviena skubos tvarka atlikta invazinė procedūra, lyginant su planuota operacija, yra susijusi su didesniu komplikacijų skaičiumi. Viena iš dažniausių komplikacijų -pooperacinis bakterinis meningitas [4,7,11]. Literatūros duomenimis, meningito ar ventrikulito išsivystymo dažnis po ISD operacijos svyruoja nuo 1 iki 45 procentų [10,12,18].…”
Section: įVadasunclassified